Bioactives of Hypericum Perforatum to Control Diabetes: In Vitro and In Vivo Biological Evaluation in Diabetic Rats - Neelam Singh; Puneet Gupta (Proceedings)
Background: Improving diabetes mellitus treatment is a significant contemporary medical and societal issue [...]